The TECHNIQUE CHARACTERIZATION AND HYDRAULIC PERFORMANCE OF PERFORATED HOSE SYSTEM FOR SUGARCANE IN COLOMBIA - Mendoza, Christian José; Carbonell, Javier Alí; Lasso, John Jairo (IRRIGA, 2020)
TECHNIQUE CHARACTERIZATION AND HYDRAULIC PERFORMANCE OF PERFORATED HOSE SYSTEM FOR SUGARCANE IN COLOMBIA CHRISTIAN JOSÉ MENDOZA1; JAVIER ALÍ CARBONELL2 E JOHN JAIRO LASSO3 1Soil and Water Engineer, Agronomy Program, Colombian Sugarcane Research Center, San Antonio Experimental Station, Road Cali – Florida km 26, Candelaria, Valle del Cauca, Colombia, christianmendozac@gmail.com 2Ex-Director Agronomy Program, Colombian Sugarcane Research Center, San Antonio Experimental Station, Road Cali – Florida km 26, Candelaria, Valle del Cauca, Colombia, jjcarbonell@cenicana.org 3Agricultural Technician, Agronomy Program, Colombian Sugarcane Research Center, San Antonio Experimental Station, Road Cali – Florida km 26, Candelaria, Valle del Cauca, Colombia, jjlasso@cenicana.org 1 ABSTRACT Sugarcane crops in Colombia are traditionally irrigated, and a higher portion of of the area with the irrigation system by furrows, where efficiency does not exceed 50% and present high application volumes per unit area. In pursuit of a more efficient use of water resources and conservation of the environment, a microirrigation system by perforated hose has been introduced recently. The objective of this research was to characterize and evaluate the performance of the perforated hose system. Therefore, to carry out this experiment, pressures 4, 5, 6, 7, and 8 PSI were evaluated, the flow in each orifice, and the water distribution in the system area. The following parameters were determined: (a) average flow rate, (b) coefficient of manufacture variation, (c) characteristic equation of the emitter/orifice, (d) distance between emitters, and (e) Christiansen Uniformity Coefficient-UC. The analyses showed coefficients of manufacture variation superior to 0.29 for all the pressures evaluated, and the UC were also very low for the system installation options in continuous furrow and alternate furrow, being superior to 43% and 52% respectively. The exponents x of the pressure versus flow equation will range from 0.119 to 0.813. Keywords. Christiansen uniformity coefficient, coefficient of variation, characteristic equation. MENDOZA, C.J.; CARBONELL, J.A.; LASSO, J.J. CARACTERIZAÇÃO TÉCNICA E DESEMPENHO HIDRÁULICO DO SISTEMA DE IRRIGAÇÃO POR MANGUEIRA PERFURADA PARA CANA-DE-AÇÚCAR NA COLÔMBIA 2 RESUMO A cultura da cana-de-açúcar na Colômbia é irriga tradicionalmente e em maior porcentagem da área com o sistema de irrigação por sulcos, onde a eficiência não excede 50% e com altos volumes de aplicação por unidade de área. Em busca de um uso mais eficiente dos recursos hídricos e da conservação do meio ambiente, um sistema de microirrigação por mangueira perfurada foi introduzido recentemente. O objetivo desta pesquisa foi caracterizar e avaliar o desempenho do sistema por mangueira perfurada. Portanto, para realizar este experimento, se avaliaram as pressões de 4, 5, 6, 7 e 8 PSI, a vazão em cada orifício e a distribuição de água na área do sistema. Os seguintes parâmetros foram determinados: (a) vazão média, (b) coeficiente de variação de fabricação, (c) equação característica do emissor / orifício, (d) distância entre emissores e (e) Coeficiente de Uniformidade de Christiansen - CUC. As análises mostraram coeficientes de variação de fabricação superiores a 0,29 para todas as pressões avaliadas, também os CUC foram muito baixos para as opções de instalação do sistema em sulco contínuo e sulco alternado superiores a 43% e 52%, respectivamente. Os expoentes x da equação pressão versus fluxo variam de 0,119 a 0,813. Palavras-chave: coeficiente de uniformidade de Christiansen, coeficiente de variação, equação característica.